More than words: conceptualizing narrative computational thinking based on a multicase study - Schlauch, Michael (2025)
This paper presents an investigation that compares and analyzes the interactions of three groups of pre-and-primary school children with three different storytelling systems. We identify emerging patterns through which they engaged in what we refer to as narrative computational thinking. The latter describes broadened aspects of narrative literacy practices that are linked to computational thinking. By applying a multicase study approach and through various vignettes, we illustrate how children applied computational thinking to understand and influence the narrative possibilities offered by the different tools. Our results illustrate circumstances under which digital storytelling activities provide a favorable basis for narrative computational thinking, and that when computational thinking functions as a scaffold for story creation, it encourages a blend of creativity and computational thinking, providing a compelling approach to introducing emerging digital literacies to young children in a narrative context.